Petrogenesa Batuan Beku Dasit Daerah Hila dan Sekitarnya, Kabupaten Maluku Tengah - Sitti Hafsa Kotarumalos; Resti Limehuwey; Warni Multi; Rimawanto Gultom; Erfin Elly (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
A daisiac rock with the presence of abundant corderite and garnet that is considered quite unusual and named ambonite after its island name (Verbeek, 1905 in Pownall, 2013). Dacite rocks are scattered on Ambon Island and its surroundings. The Research Area is located in Hila Village, Central Maluku Regency located on Ambon Island. This study aims to determine the characteristics of petrogenesis of dasite rocks and their tectonic order. The methods used are studio analysis, geomorphological analysis, and geological structure analysis and laboratory analysis methods in the form of petrographic analysis, and XRF (X-Ray Fluoresence) analysis. Dacite rocks have porphyritic, intersetal, poikilitic, and reaction rim mineral textures. It also has a plagioclate microtexture in the form of coarse sieve, oscillatory zoning, rounded zone corners and glomerocrysts. Geochemically, this rock has an affinity  for alkaline calc  magma because it has a moderate K2O content and a fairly high SiO2 content. Ambonite rocks undergo magma differentiation in the form of fractional crystallization as seen from the harker diagram of the main oxide element. Based on its magma affinity of calc alkaline and its TiO2 content of less than 1%, it is indicated that ambonite rocks were formed in the archipelago. This order is assumed to have formed as a result of convergent interactions during the late Miocene.